Serious Adverse Drug Reactions and Safety Signals in Children: A Nationwide Database Study - Vieira, Jean Mendes de Lucena; de Matos, Guacira Corrêa; da Silva, Fabrício Alves Barbosa; Bracken, Louise E.; Peak, Matthew; Lima, Elisangela da Costa (Frontiers in Pharmacology, 2020)
Children are more exposed to inappropriate medicines use and its harms. Spontaneous reporting of suspected Serious Adverse Drug Reactions (SADRs) increases knowledge and prevention of pharmacotherapy risk. Disproportionality measures are useful to quantify unexpected safety issues associated with a given drug-event pair (signals of disproportionality). This cross-sectional study aimed to assess SADRs reporting and safety signals for Brazilian children 0-12 years old notified between January 2008 and December 2013 from the system of the Brazilian Surveillance Agency (Notivisa). Information from serious reporting (gender and age of the patient, event description, suspected drug) was included. Disproportionality analysis based on Reporting Odds Ratios with a confidence interval of 95% were conducted to identify possible signals of disproportionate reporting (SDR). Almost 30% from 1977 suspected SADR was related to babies (0-1-year-old). 69% of reports happened with intravenous dosage forms and 35% of suspected SADRs involved off label use according to age. Laronidase, miglustat, imipenem/cilastatin, and clofarabine were involved in six or more suspected among 75 deaths reported. There were 107 SDR of which 16 events (15%) were not described in the product labels. There was a relatively higher number of SADRs in children, compared with studies from other countries. SDR found (especially pairs drug-event ‘imipenen/cilastatin–pneumonia’ and ‘laronidase–respiratory insufficiency’) should be more investigated. Reports of SADRs with IV dosage forms and OL drug use observed suggest the need for research and the use of better dosage forms for children in Brazil.